Between tradition and innovation: Sustainability and humanitarianism in the architecture of Shigueru Ban - Dórea , Marcela Moreira (Technical and Scientific Journal Green Cities, 2024)
This article analyzes the architectural practice of Shigeru Ban, emphasizing his sustainable and humanitarian approach in the face of natural disasters. The focus is on the intersection of architecture and sustainability, addressing how Ban utilizes innovative and accessible solutions in his projects. The research was conducted through a bibliographic review of primary and secondary sources discussing Ban’s works, his design philosophy, and his contributions to sustainable architecture. The critical analysis was based on a theoretical approach that integrates concepts of sustainability, ethics, historiography, and the philosophy of the Japanese building tradition. It proposes an ethical perspective for sustainable architectural practice so that it does not merely become a product of a green market. The architecture produced by Shigeru Ban provides pathways for sustainable and accessible architectural practices in different parts of the world, promoting the restoration of dignity and well-being for those who use the designed spaces.